SIMULASI SOLUSI PERSAMAAN DIFERENSIAL BIASA ORDE TINGGI DENGAN METODE RUNGE- KUTTA -FEHLBERG DAN MODIFIKASI EULER - Sitompul, Hery Andi; Siahaan, Enzo W. B (Jurnal Sains dan Teknologi ISTP, 2024)
Modified Euler and Runge-Kutta-Fehlberg methods are generally used to determine solutions to first order ordinary differential equations numerically. In this study, simulations will be carried out to apply these two methods to determine numerical solutions to higher order differential equations through several examples. It was found that both methods can approach the exact solution well, and the Runge-Kutta-Fehlberg method provides better results based on the average percentage of error produced.